The Cambridge companion to law in the Hebrew Bible - Wells, Bruce (Cambridge companions to religion, 2024)
"This book is for students, scholars, and general readers who are interested in the legal texts and ideas of the Hebrew Bible (Old Testament). The book explains the nature and history of biblical law, the legal significance of its rules, and its influence on early Judaism and Christianity"--